A Jurisdictional Approach to Indonesia’s Wildlife Trade - Vega Vanessa Teodoree; Tantimin Tantimin (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Indonesia is one of the countries that lack a sense of concern for animals due to the rampant wildlife trade that occurs in the country. Bushmeat is not consumable since it is not regulated inside the Indonesian Law Number 18 of 2012 concerning food (hereinafter abbreviated as Law on Consumables). Various traded wild animals are believed by several individuals to have contained many good properties when consumed and can cure various diseases. But Bushmeat is a source of diseases such as Emerging Infectious Diseases (EIDs) and Coronavirus Disease (Covid-19) while also endangering the preservation of biodiversity. This bushmeat trade also sells the meat of protected endangered animals, which are proven to have violated Law Number 5 of 1990 concerning Conservation of Biological Natural Resources Article and its Ecosystem (hereinafter abbreviated as Law on Conservation of Biological Natural Resources Article and its Ecosystem), as well as other laws. The research method applied in this research would be normative juridical, which uses positive Law as a source of existing Law. The goal of this research is to understand the regulations related to Bushmeat trading based on the Law and the application towards bushmeat dealers established in Indonesia's Law Number 41 of 2014 concerning Amendments to Law Number 18 of 2009 concerning Animal Husbandry and Health (hereinafter abbreviated as Law on Livestock and Animal Health), Law on Consumables, Law on Conservation of Biological Natural Resources Article and its Ecosystem, Government Regulation Number 7 of 1999 concerning Preservation of Plant and Animal Species, Law Number 8 of 1999 concerning Consumer Protection (hereinafter abbreviated as Law on Consumer Protection) and the Criminal Code.